2023
DOI: 10.1159/000528920
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Atopic Diseases in Patients with Hidradenitis Suppurativa: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Background Hidradenitis suppurativa (HS) and allergic diseases were considered to have different immune pathways involved. However, available evidences seemed to be inconsistent and the association was not well-developed yet. Objective To perform a systematic review and meta-analysis to evaluate the association between HS and atopic diseases, including asthma, atopic dermatitis, allergic rhinitis and conjunctivitis. Methods Search in databases including PubMed, Embase and Web of Science were performed. Synon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Although the pathogenesis of HS has not been fully understood, it was pointed out that sustained inflammatory reaction within dermatological diseases had the potential to trigger systemic immunological involvement, consequently fostering the emergence of comorbidities in various organ systems ( 22 24 ). Given these conditions, the issue of HS comorbidities had long been discussed and was acknowledged as intricate, encompassing several different functional problems including allergic status ( 25 ), gastrointestinal dysfunctions ( 26 , 27 ), and renal diseases ( 28 ). Among the comorbidities of HS, integrated pieces of evidence had suggested that spondyloarthritis and rheumatoid arthritis were of high prevalence and incidence in the HS population ( 6 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathogenesis of HS has not been fully understood, it was pointed out that sustained inflammatory reaction within dermatological diseases had the potential to trigger systemic immunological involvement, consequently fostering the emergence of comorbidities in various organ systems ( 22 24 ). Given these conditions, the issue of HS comorbidities had long been discussed and was acknowledged as intricate, encompassing several different functional problems including allergic status ( 25 ), gastrointestinal dysfunctions ( 26 , 27 ), and renal diseases ( 28 ). Among the comorbidities of HS, integrated pieces of evidence had suggested that spondyloarthritis and rheumatoid arthritis were of high prevalence and incidence in the HS population ( 6 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of HS involved the elevation of proinflammatory cytokines that could trigger subsequent immunological cascades (21). Although the pathogenesis of HS has not been fully understood, it was pointed out that sustained inflammatory reaction within dermatological diseases had the potential to trigger systemic immunological involvement, consequently fostering the emergence of comorbidities in various organ systems (22)(23)(24). Given these conditions, the issue of HS comorbidities had long been discussed and was acknowledged as intricate, encompassing several different functional problems including allergic status (25), gastrointestinal dysfunctions (26,27), and renal diseases (28).…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher predominant gender difference [1]. In HS patients, involvement of comorbidities in various organ system were commonly observed [2][3][4][5]. This may be attributed to the systemic inflammatory nature of HS pathogenesis.…”
Section: Ivyspringmentioning
confidence: 99%
“…According to current evidences, the prevalence ranges from 0.00033% to 4.10% in different studies and populations, with a female-predominant gender difference 1 . In HS patients, involvement of comorbidities in various organ system were commonly observed 2 - 5 . This may be attributed to the systemic inflammatory nature of HS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions manifest themselves through a dominant immune response of type 2 T (Th2), orchestrated by cytokines such as IL-4 and IL-13 5 . Although HS has historically been associated with distinct inflammatory pathways characterized by cytokines like IL-1β, TNFα, IFN-γ, and IL-17/22, a recent meta-analysis provided evidence regarding the association between HS and atopic dermatitis and asthma, challenging the conventional separation of these conditions 1 , 6 .…”
Section: Introductionmentioning
confidence: 99%